CLINICAL THINKING IN TEACHING OF PEDODONTIA ON THE POSTGRADUATE STAGE OF EDUCATION - Шешукова, О.В. (World of Medicine and Biology, 2015)
The importance of development of clinical thinking in dentists at a postdegree stage of education is highlighted in the article. Features which have to be inherent in the identity of the doctor, forming his ability to clinical thinking are defined, some methods of its development are offered. The current system of clinical training has to be focused on assimilation of methodology of treatment, but not on ensuring volume of knowledge. The clinical thinking has to be developed in the course of study and be improved during the life-time professional medical activity.
Keywords: clinical thinking; dentist; children